KnowledgeBoat Logo

Mathematics

Prove the following:

11 + tan2A+11 + cot2A\dfrac{1}{\text{1 + tan}^2 A} + \dfrac{1}{\text{1 + cot}^2 A} = 1

Trigonometrical Ratios

16 Likes

Answer

Solving L.H.S. of the equation : 11 + tan2A+11 + cot2A\dfrac{1}{\text{1 + tan}^2 A} + \dfrac{1}{\text{1 + cot}^2 A} = 1.

=11+sin2Acos2A+11+cos2Asin2A=1cos2A+sin2Acos2A+1sin2A+cos2Asin2A=cos2Asin2A+cos2A+sin2Asin2A+cos2A=sin2A+cos2Asin2A+cos2A=1.\phantom{=} \dfrac{1}{1 + \dfrac{\text{sin}^2 A}{\text{cos}^2 A}} + \dfrac{1}{1 + \dfrac{\text{cos}^2 A}{\text{sin}^2 A}} \\[1em] = \dfrac{1}{\dfrac{\text{cos}^2 A + \text{sin}^2 A}{\text{cos}^2 A}} + \dfrac{1}{\dfrac{\text{sin}^2 A + \text{cos}^2 A}{\text{sin}^2 A}} \\[1em] = \dfrac{\text{cos}^2 A}{\text{sin}^2 A + \text{cos}^2 A} + \dfrac{\text{sin}^2 A}{\text{sin}^2 A + \text{cos}^2 A} \\[1em] = \dfrac{\text{sin}^2 A + \text{cos}^2 A}{\text{sin}^2 A + \text{cos}^2 A} \\[1em] = 1.

Since, L.H.S. = R.H.S.

Hence, proved that 11 + tan2A+11 + cot2A\dfrac{1}{\text{1 + tan}^2 A} + \dfrac{1}{\text{1 + cot}^2 A} = 1.

Answered By

9 Likes


Related Questions